Knee muscles isokinetic evaluation after a six-month regular combined swim and dry-land strength training period in adolescent competitive swimmers - Dalamitros, A. A.; Manou, V.; Christoulas, K.; Kellis, S. (Journal of Human Kinetics, 2015)
Previous studies demonstrated significant increases in the shoulder internal rotators` peak torque values and unilateral muscular imbalances of the shoulder rotators after a competitive swim period. However, there are no similar data concerning the knee muscles. The purpose of the current study was to examine the effects of a six-month training period on knee flexor and extensor peak torque values, examine a possible bilateral strength deficit and evaluate the unilateral strength balance in competitive swimmers. Eleven male adolescent swimmers (age: 14.82 ± 0.45 years) were tested for concentric knee extension and flexion peak torque (60°/s) with an isokinetic dynamometer, before and after a regular combined swim and dry-land strength training period. A trend towards greater improvements in the knee extensor compared to flexor muscles peak torque was observed. Furthermore, the bilateral strength deficit remained almost unchanged, whereas unilateral strength imbalance was increased for both limbs. However, all results were nonsignificant (p > 0.05). According to the data presented, a six-month regular combined swim and dry-land strength training period caused non-significant alterations for all the parameters evaluated during isokinetic testing. This study highlights the fact that competitive adolescent swimmers demonstrated unilateral knee strength imbalances throughout a long period of their yearly training macrocycle.